Sustainable innovation for industry 6.0 - Gupta, Sachin; Moses, Olayinka; Sharma, Asha; Sharma, Raj Bahadur 1936- (Advances in business information systems and analytics (ABISA) book series, 2024)
The landscape of Industry 6.0 is rapidly evolving, and businesses are facing a significant challenge of integrating sustainable practices into their operations. This task is further complicated by the need to navigate the complex web of sustainability goals and green technologies. Many companies need assistance understanding how Industry 6.0 can be leveraged to meet these goals, promote innovation, and drive economic growth. Sustainable Innovation for Industry 6.0 provides diverse insights on the intricate relationships between Industry 6.0's sustainable innovation functions, empowering companies to capitalize on sustainability and manage sustainable development effectively by providing a comprehensive roadmap. It offers a unique perspective on how businesses can use Industry 6.0 technologies to incorporate sustainability into their practices, thus ensuring long-term success and environmental stewardship.